Identification of the Plasmodium falciparum rhoptry neck protein 5 (PfRON5) (2011)
Gathering knowledge about the proteins involved in erythrocyte invasion by Plasmodium merozoites is the starting point for developing new strategies to control malarial disease. Many of these proteins have been studied in Toxoplasma gondii, where some belonging to the Moving Junction complex have been identified. This complex allows a strong interaction between host cell and parasite membranes, required for parasite invasion. In this genus, four rhoptry proteins (RON2, RON4, RON5 and RON8) and one micronemal protein (TgAMA-1) have been found as part of the complex. In Plasmodium falciparum, RON2 and RON4 have been characterized. In the present study, we identify PfRON5, a ~. 110. kDa protein which is expressed in merozoite and schizont stages of the FCB-2 strain. © 2010 Elsevier B.V.